Managing wetlands an ecological economics approach - Turner, R. Kerry; Bergh, Jeroen C. J. M. van den, 1965-; Brouwer, Roy.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar Pub., 2003)
The extensive destruction of wetlands across Europe represents a significant loss of biodiversity along with its related economic, cultural, ethical and scientific benefits. This volume addresses the critical issues surrounding this environmental change process, employing a range of analytical methods drawn from a variety of disciplines which bridge the social and natural science divide.
pt. I. Methodological issues and wetland ecosystem management -- pt. II. Case studies of ecological-economic approaches to wetland ecosystem management.
Includes bibliographical references and index.
Keywords: Wetland management -- Economic aspects; Electronic books